GRUPO DE HIPERDIA: EDUCANDO PARA VIDA - Brunna Soares De Souza; Marcela Sfalsin das Chagas; Cosme Baptista Domingos; Elisa Santiago da Silva (Revista de Pesquisa Cuidado é Fundamental Online)
GRUPO DE HIPERDIA: EDUCANDO PARA VIDA Brunna  Soares de Souza1 Marcela Sfalsin das Chagas2 Elisa Santiago da Silva3 Cosme Baptista Domingos4